2018
DOI: 10.3390/ijms19102869
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Metformin in the Failing Heart

Abstract: Accumulating evidence shows that metformin is an insulin-sensitizing antidiabetic drug widely used in the treatment of type 2 diabetes mellitus (T2DM), which can exert favorable effects on cardiovascular risk and may be safely used in patients with heart failure (HF), and even able to reduce the incidence of HF and to reduce HF mortality. In failing hearts, metformin improves myocardial energy metabolic status through the activation of AMP (adenosine monophosphate)-activated protein kinase (AMPK) and the regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 157 publications
(213 reference statements)
2
60
0
Order By: Relevance
“…Reports indicated that patients with diabetes account for almost one-third of heart failure cases (99). It has been shown that metformin improves the myocardial energy status through ameliorating cellular lipid and glucose metabolism via AMPK (100). Recently, a randomized controlled trial in patients with coronary artery disease without diabetes demonstrated that metformin significantly reduces left ventricular hypertrophy (LVH), one of the most powerful prognostic factors in coronary artery disease.…”
Section: Metformin and Cardiovascular Diseasesmentioning
confidence: 99%
“…Reports indicated that patients with diabetes account for almost one-third of heart failure cases (99). It has been shown that metformin improves the myocardial energy status through ameliorating cellular lipid and glucose metabolism via AMPK (100). Recently, a randomized controlled trial in patients with coronary artery disease without diabetes demonstrated that metformin significantly reduces left ventricular hypertrophy (LVH), one of the most powerful prognostic factors in coronary artery disease.…”
Section: Metformin and Cardiovascular Diseasesmentioning
confidence: 99%
“…Other examples of the relationships between microbiota and atherosclerosis are the administration of metformin and whole grains; metformin is a biguanide antidiabetic drug widely used in adults that have shown to exert positive effects to fight against CVD risk and that might be used safely in patients with heart failure and even reduce its occurrence or mortality, not only by direct effects [140], but also because of the possible effects produced through gut microbiota remodeling [141]. Also, the diet seems to be a potential therapy to diminish the risk of CVD since a study on a specific population of Danish adults showed that a diet abundant in whole grain compared to refined grain reduces body mass and systemic inflammation [142], which are risk factors to a bad prognosis of CVD.…”
Section: Microbiota and Atherosclerosismentioning
confidence: 99%
“…A more recent opinion, however, considers the risk of metformin in diabetic patients with heart failure as minimal and suggests that the cardioprotective benefit outweighs this risk [97]. Indeed, the metabolic and anti-fibrotic effects of metformin on the failing heart have been reviewed, encouraging large-scale clinical trials in diabetic patients with heart failure [98]. Moreover, metformin improves cardiac LVEF and survival in mice with ischaemiainduced heart failure [99].…”
Section: Metforminmentioning
confidence: 99%